2018
DOI: 10.7759/cureus.2011
|View full text |Cite
|
Sign up to set email alerts
|

Pure Squamous Cell Carcinoma of the Gallbladder Masquerading as a Hepatic Mass

Abstract: Gallbladder (GB) carcinomas are adenocarcinomas (AC) in the majority of cases. Adenosquamous carcinoma (ASC) and pure squamous cell carcinoma (SCC) of the gallbladder are rarely encountered and comprise 1-3% of gallbladder cancer cases.  Pure squamous cell carcinoma of the gallbladder is rarer with less than 1% of the incidence. Most of the published literature is based on case reports and case series. The survival rates of ASC and SCC of the gallbladder are significantly lower (mean of five months) compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Pure SCC might derive de novo from the metaplastic transformation of normal glandular cells through the intermediate stages of dysplasia, culminating in cancer, 7,15,24 while ASC might arise from squamous differentiation within pre‐existing AC cells 25 . Recent studies on molecular mechanisms suggested that CD109 and FGFBP1 may be involved in tumour pathogenesis and yield novel therapeutic targets 10,23,26–29 …”
Section: Discussionmentioning
confidence: 99%
“…Pure SCC might derive de novo from the metaplastic transformation of normal glandular cells through the intermediate stages of dysplasia, culminating in cancer, 7,15,24 while ASC might arise from squamous differentiation within pre‐existing AC cells 25 . Recent studies on molecular mechanisms suggested that CD109 and FGFBP1 may be involved in tumour pathogenesis and yield novel therapeutic targets 10,23,26–29 …”
Section: Discussionmentioning
confidence: 99%
“…If SCCG is identified early, surgical resection is potentially curative and can improve the prognosis. 10 Unfortunately, only a small population of patients with localized disease benefit from surgical resection. Most patients with gallbladder carcinoma are diagnosed at an advanced stage and do not have the opportunity to undergo the radical surgical operation.…”
Section: Discussionmentioning
confidence: 99%
“…Gall stones appear to play a major, probably due to chronic irritation, role as evidenced by the fact that approximately 90% of SCCs invariably have associated cholelithiasis [8] . It is mostly associated with cholesterol stones as shown by Cariati et al [9] The high incidence in countries like India could be explained by the association with parasitic infections [10] . The other risk factors are adenoma, porcelain gall bladder, cholesytoenteric fistula, ulcerative colitis, anomalous biliopancreatic junction.…”
Section: Discussionmentioning
confidence: 97%